2022
DOI: 10.1038/s41467-022-34578-x
|View full text |Cite
|
Sign up to set email alerts
|

SAMHD1 deacetylation by SIRT1 promotes DNA end resection by facilitating DNA binding at double-strand breaks

Abstract: Sterile alpha motif and HD domain-containing protein 1 (SAMHD1) has a dNTPase-independent function in promoting DNA end resection to facilitate DNA double-strand break (DSB) repair by homologous recombination (HR); however, it is not known if upstream signaling events govern this activity. Here, we show that SAMHD1 is deacetylated by the SIRT1 sirtuin deacetylase, facilitating its binding with ssDNA at DSBs, to promote DNA end resection and HR. SIRT1 complexes with and deacetylates SAMHD1 at conserved lysine 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 106 publications
(198 reference statements)
1
14
0
Order By: Relevance
“…Given its described function as a dNTPase, it has been mysterious why loss-of-function mutations in SAMHD1 are associated with AGS, SLE, oncogenesis, and chronic DNA damage in cells. ,,, Insight into this question was provided by two studies that revealed secondary DNA damage repair (DDR) functions of SAMHD1, that if inhibited, could lead to additional antitumor effects . One repair function of SAMHD1 is to promote homologous recombination by its association with double strand break (DSB) foci, , which helps explain the association of SAMHD1 with oncogenesis and DNA damage. Another role for SAMHD1 is in coordinating the restart of stalled replication forks (RFs).…”
mentioning
confidence: 99%
“…Given its described function as a dNTPase, it has been mysterious why loss-of-function mutations in SAMHD1 are associated with AGS, SLE, oncogenesis, and chronic DNA damage in cells. ,,, Insight into this question was provided by two studies that revealed secondary DNA damage repair (DDR) functions of SAMHD1, that if inhibited, could lead to additional antitumor effects . One repair function of SAMHD1 is to promote homologous recombination by its association with double strand break (DSB) foci, , which helps explain the association of SAMHD1 with oncogenesis and DNA damage. Another role for SAMHD1 is in coordinating the restart of stalled replication forks (RFs).…”
mentioning
confidence: 99%
“…Previous studies have also found that elephant cells repair DNA damage much faster than other smaller-bodied mammals (Francis et al, 1981; Hart and Setlow, 1974; Promislow, 1994), suggesting that DNA damage repair genes may have derived functions in elephants. Among the positively selected and rapidly evolving genes, for example, are RIF1 , which cooperates with TP53BP1 to promote DNA repair by non-homologous end joining (NHEJ) in the G 1 and S phases of the cell cycle (Escribano-Díaz et al, 2013; Feng et al, 2013; Virgilio et al, 2013), the multifunctional exonuclease EXO1 , which is involved in DNA damage checkpoint progression, mismatch repair (MMR), translesion DNA synthesis (TLS), nucleotide excision repair (NER), and limits end resection of double-strand breaks thereby facilitating repair via error-free homologous recombination (HR) rather than error-prone NHEJ (Keijzers et al, 2018; Tomimatsu et al, 2017), MLH1 , part of PMS2 MMR complex that generates single-strand breaks near the mismatch and entry points for EXO1 to degrade the strand containing the mismatch (Kadyrov et al, 2006; Kansikas et al, 2011; Sacho et al, 2008), NEK4 , which regulates a unique ATM/ATR-independent DNA damage checkpoint and the induction of replicative senescence in response to double-stranded (DSB) DNA damage (Chen et al, 2011; Tomimatsu et al, 2017), KAT5 , an acetyltransferase that plays an essential role in DNA damage repair by acetylating and activating ATM and the canonical DSB repair pathway (Sun et al, 2005)and SAMHD1 which promotes DNA end resection to facilitate DSB repair by HR (Daddacha et al, 2017; Kapoor-Vazirani et al, 2022). Similarly, long-lived and cancer-resistant Bowhead whales, which have a maximum lifespan of over 200 years (George et al, 1999), have evolved cells that repair double-strand breaks with high efficiency and accuracy compared to many other mammals (Firsanov et al, 2023), suggesting that the evolution of DNA damage repair genes may be a common route to evolve cancer resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The role of SAMHD1 in HR is to promote DNA end resection that generates substrates required for HR via recruitment of CtIP protein to sites of DNA damage (35). In addition to regulation by phosphorylation, the role of SAMHD1 in HR can be controlled by SIRT1 deacetylation as this facilitates SAMHD1 binding to double strand DNA breaks (36). Moreover, SAMHD1 SUMOylation by PIAS1 also regulates its DNA binding and anti-viral activity (48).…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylation of SAMHD1 on threonine 592 (T592) by CDK1 or CDK2 converts SAMHD1 into a homologous recombination factor promoting the recruitment of MRE11 to sites of damaged DNA for end resection (34, 35). The binding to DNA for end resection is promoted by deacetylation of SAMHD1 by SIRT1, a class III deacetylase (36). SIRT1 can deacetylate HPV16 E2 to promote stability and boost E2 replication function (8).…”
Section: Introductionmentioning
confidence: 99%